Reduce Heat Stress on Broilers During Transport by Supplying Drinking Water - Insan Mujahid Afnan; Niken Ulupi; Rudi Afnan (Jurnal Agripet, 2022)
ABSTRACT. The transportation process causes heat stress in broilers. This research aims to test the effectiveness of the drinking water supply system for broilers during transport to reduce the effects of heat stress caused by the transportation process. Broilers are grouped into four treatments: morning transport with water (T1), morning transport without water (T2), afternoon transport with water (T3), and afternoon transport without water (T4). Results show that broilers consume more water (317.26 ml/bird/hour) during morning than during afternoon transport (61.53 ml/ bird/hour). However, these numbers are estimated to be lower, with water spillage contributing to the high consumption, especially during morning transport. Rectal temperature for birds is lower in T1 and T3 broilers compared to T2 and T4 broilers, although still within normal range. A decrease in hematocrit and blood glucose levels while still at normal levels is observed for all treatment groups. An increase in the ratio of heterophile and lymphocyte (HL ratio) is observed within the normal range except for T1. Percentage of body weight loss is lower on broilers with access to water: T1 (3.5%) and P3 (4.4%) compared to broilers without access to water: T2 (4.0%) and T4 (5.0%) in the same time of transport although not statistically significant (P0.05). Based on weight loss percentage, it can be concluded that water intake during transport has some effectiveness in reducing heat stress with the best results shown on broilers transported in the morning with drinking water..(Mengurangi cekaman panas pada ayam broiler saat transportasi melalui pemberian air minum)ABSTRAK. Proses transportasi menyebabkan ayam mengalami cekaman panas. Penelitian ini bertujuan untuk mengkaji efektifitas pemberian air minum selama transportasi dalam upaya mengurangi dampak cekaman panas dan meningkatkan kesejahteraan hewan dengan cara mengurangi dehidrasi dan cekaman yang disebabkan proses transportasi pada ayam broiler. Ayam dikelompokkan menjadi empat perlakuan: transportasi pagi dengan air minum (T1), transportasi pagi tanpa air minum (T2), transportasi siang dengan air minum (T3), dan transportasi pagi tanpa air minum (T4). Hasil menunjukkan ayam lebih banyak mengonsumsi air (317,26 ml/ekor/jam) pada transportasi pagi daripada transportasi siang (61,53 ml/ekor/jam). Namun, nilai ini diestimasi lebih rendah dari yang didapatkan, dengan air yang tumpah berkontribusi terhadap tingginya konsumsi air, terutama pada transportasi pagi hari. Suhu rektal lebih rendah pada broiler T1 dan T3 dibandingkan T2 and T4 namun berada dalam rentang normal. Penurunan kadar glukosa darah dan hematokrit terjadi pada seluruh perlakuan. Peningkatan rasio HL terjadi pada seluruh perlakuan kecuali T1. Persentase penurunan bobot badan lebih rendah pada ayam yang diberi air minum T1 (3,5%) dan T3 (4,4%) dibandingkan dengan ayam yang tidak diberi air minum T2 (4,0%) dan T4 (5,0%) pada waktu transportasi yang sama meskipun secara statistik tidak signifikan (P0,05). Berdasarkan perbedaan persentase penurunan bobot badan, dapat disimpulkan bahwa konsumsi air mengurangi dampak cekaman panas yang dialami ayam broiler selama transportasi dengan hasil terbaik didapatkan pada transportasi pagi dengan air minum.